Optimising the performance of genetically engineered Aedes aegypti - Black, I (2017)
The mosquito Aedes aegypti is the primary worldwide vector of dengue fever, of which there are an estimated 390 million infections annually. Traditional vector control methods have been unsuccessful in preventing Ae. aegypti from posing a serious threat to human health worldwide, and as a result increasing emphasis is being placed on new control technologies. One of these is RIDL® (Release of Insects carrying a Dominant Lethal), a modified form of the sterile insect technique. Released RIDL males of strain OX513A are genetically engineered to possess a repressible lethal construct. Upon mating with a wild female, the construct is inherited by the offspring, causing their death. The RIDL strategy depends on the mass production and release of vigorous male insects, capable of competing with wild males to mate with wild females. Chapter 2 investigates how rearing conditions can influence the size, asymmetry, quantity, and timing of OX513A mosquitoes produced. Chapter 3 describes the design and testing of devices for the release of these adult males, and their implementation during the world’s first release of transgenic mosquitoes. Chapter 4 discusses how the modification of male size and nutritional status may affect subsequent performance, and how these changes to male vigour will be assessed in subsequent chapters. Chapter 5 measures changes in competitiveness by examining longevity. Larger males lived longer, and longevity was increased by increasing the duration of the initial sugar feed. Chapter 6 examines the potential improvements in male performance by measuring the flight capacity of OX513A males, using a purpose-built mosquito flight mill. Male size or nutritional status was not found to affect flight capacity, although light intensity was unexpectedly found to modulate the flight speed of the males. Finally, Chapter 7 examines potential improvements in the mating performance of male OX513A Ae. aegypti. When OX513A males and wild-type males were placed in direct competition for virgin females, smaller OX513A males were found to have a significant mating advantage over larger wild-type males. The results of all three of these performance measures are discussed with relevance to field releases. The results presented in this thesis improve current knowledge of how the performance of male mosquitoes can be effectively measured and improved. This is a vital part of ensuring the success of male-release vector control strategies such as RIDL.